The expressibility of modality in representational complement clauses in Brazilian Portuguese - Bastos, Sandra D. Gasparini; Galvão, Vânia C. Casseb; Gonçalves, Sebastião Carlos L.; Hattnher, Marize M. Dalli’Aglio; Hengeveld, Kess; Sousa, Gisele Cássia de; Vendrame, Valéria (ALFA: Revista de Linguística, 2009)
This paper deals with the (im)possibility of expressing a variety of modal categories within the context of the layering approach to complementation in Functional Discourse Grammar (FDG).Our hypothesis is that modal expressions in complement clauses only pertain to operator or modifier classes of the highest layer relevant for that type of embedded construction and for all lower levels. In order to test this hypothesis, occurrences of complement clauses in two databases of spoken Brazilian Portuguese are analyzed. The investigation of this hypothesis is restricted to representational complement clauses.